The Effect of Capital Structure, Profitability, and Size to Firm Value of Property and Real Estate at Indonesia Stock Exchange In the Period of 2012-2018 - Santi Oktaviani Halfiyyah; Iman S. Suriawinata (Indonesian Journal of Business, Accounting and Management (IJBAM), 2019)
The purpose of this research is to determine whether the Capital Structure, Profitability Ratio, and Size both individually the firm value of the property and real estate in the Indonesia Stock Exchange (BEI) period 2012-2018.Capital Structure is represented by using Longterm Debt to Equity Ratio (LDER), Profitability is represented by using Return On Equity (ROE), Size is represented by using logaritma natural (Ln). By using purposive sampling technique, the population of 53 companies and the sample of 30 companies with the period of research are 7 years the total ampunt of succesfully observed samples has been reduced to 210 samples of data. This causal-comparative research uses panel data with secondary data that collected by using documenting and archiving techniques from Indonesian Capital Market Electronic Library. Multiple regression estimation method from panel data used in this research is Fixed Effect Model final.This research shows that Capital Structure effect negative to firm value, Profitability effect positif to firm value, Size effect negative to firm value individually affect the property and real estate sector in the period of 2012-2018.